Principles of hydraulic systems design - Chapple, Peter (Fluid mechanics collection., 2015)
Fluid power systems are manufactured by many organizations for a very wide range of applications, which often embody differing arrangements of components to fulfill a given task. Hydraulic components are manufactured to provide the control functions required for the operation of a wide range of systems and applications.